2013
DOI: 10.1523/jneurosci.4828-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

GDNF and Endothelin 3 Regulate Migration of Enteric Neural Crest-Derived Cells via Protein Kinase A and Rac1

Abstract: Enteric neural crest-derived cells (ENCCs) migrate from the anterior foregut in a rostrocaudal direction to colonize the entire gastrointestinal tract and to form the enteric nervous system. Genetic approaches have identified many signaling molecules regulating the migration of ENCCs; however, it remains elusive how the activities of the signaling molecules are regulated spatiotemporally during migration. In this study, transgenic mice expressing biosensors based on Förster resonance energy transfer were gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 47 publications
2
37
0
Order By: Relevance
“…We previously established a method to generate transgenic mice expressing FRET biosensors, with which the time lapse of activity changes in protein kinases can be imaged (25,26). To achieve dMSN-and iMSN-specific labeling of the PKA and ERK FRET biosensors, we created two flox lines of transgenic mice, floxed-AKAR3EV (PKA) and floxed-EKAREV (ERK) (27), both of which contained a nuclear export signal to localize these kinases in the cytoplasm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We previously established a method to generate transgenic mice expressing FRET biosensors, with which the time lapse of activity changes in protein kinases can be imaged (25,26). To achieve dMSN-and iMSN-specific labeling of the PKA and ERK FRET biosensors, we created two flox lines of transgenic mice, floxed-AKAR3EV (PKA) and floxed-EKAREV (ERK) (27), both of which contained a nuclear export signal to localize these kinases in the cytoplasm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanisms must be dynamically regulated because cells at the ENCDC migration wavefront behave differently from cells behind the wavefront. Recent, elegant studies of Förster resonance energy transfer have confirmed that PKA, RAC1, and CDC42 are differentially activated in migrating ENCDCs according to proximity to the wavefront (68). These proteins regulate the mode of cell migration (69,70) and the efficiency of bowel colonization.…”
Section: Intracellular Signaling and Migrationmentioning
confidence: 99%
“…These proteins regulate the mode of cell migration (69,70) and the efficiency of bowel colonization. Interestingly, both PKA inhibition and exogenous cAMP analogs slow ENCDC migration in organ culture (68,71), but critical PKA targets in this context are not known. This suggests that localized PKA activation or moderate activation is needed to support migration.…”
Section: Intracellular Signaling and Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…FRET imaging under twophoton excitation microscopy was performed as described previously (Goto et al, 2013). Samples were maintained in an incubation chamber (Tokai Hit, Japan) and imaged using a BX61WI/FV1000 upright microscope equipped with 606 water-immersion objective (LUMPlanFLN; Olympus, Japan) connected to a Mai Tai DeepSee HP Ti:sapphire Laser (Spectra Physics, Mountain View, CA).…”
Section: Fret Imagingmentioning
confidence: 99%